PENGARUH KETEKUNAN KOMITE AUDIT DAN AUDIT EFFORT PADA FEE AUDIT: (Studi pada Perusahaan Infrastruktur yang Terdaftar di Bursa Efek Indonesia Periode 2020-2022) - Komang, Cynthia Prisilia Winawan; Krisnadewi, Komang Ayu (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
The amount of audit fee should be determined as well as possible to obtain a good audit quality as an unusual amount of auditing fee will lower the quality of the audit. Determining the influence of audit committee persistence and audit effort on audit fee was the goal of this research. Profitability is the control variable of this research. The research covered infrastructure companies on the Indonesian Stock Exchange in the period 2020-2022 registered as many as 67 companies. Non-probability sampling methods becomes a method of sample determination, with purposive sampling technique. The financial reports and annual reports of infrastructure companies are documented for the collection of research data. The research analyzed 64 samples. This research applies descriptive statistical analysis technique, classical assumption test, double linear regression test, model validity test (F test), determination coefficient test, and hypothesis test (t test). The results of the research can explain the persistence of the audit committee influence the audit fee positively and significantly. Audit effort does not influence audit fee significantly, and profitability influence audit fee positively but not significantly. The research implies the need for regular audit committee meetings to help auditor identify the auditing risk to companies, thus helping to determine an appropriate audit fee.